Perencanaan Strategis Sistem Informasi untuk Peningkatan Layanan Pelanggan pada UMKM Food Mood - Hendry Kus Hermawan; Krisna Bagus Samboro; Bayu Effendi; M. Fikriyadi Maulana; Ito Setiawan (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
This study develops a strategic information system plan to improve customer service at the Food Mood MSME in the food and beverage sector. The Ward and Peppard framework is used to map the business and technology environment through Value Chain, SWOT, PEST, and Porter's Five Forces analyses, which are then broken down into Critical Success Factors and measurable key performance indicators. The research design is a qualitative case study with semi-structured interviews with the owner and employees, observations during peak hours, and a review of operational documents. The mapping results in a prioritized portfolio that places a cloud-based point-of-sale system integrated with QRIS, a lightweight inventory and procurement module, a kitchen display system, and basic accounting as the foundation, followed by a mini customer relationship management and loyalty program, online channel integration, a sales dashboard, and simple demand forecasting. The formulated performance targets include a wait time of no more than eight minutes, an order error rate below one percent, stock-outs of less than one day per month, and 100% transaction recording. The suggested three-month roadmap is operational and provides immediate benefits in terms of increased service speed, data accuracy, and potential customer retention, while also confirming the relevance of Ward and Peppard's approach for the Indonesian MSME context.